Exploring the practice of integrated community chronic disease management model in Shanghai - CHENG Minna; SUI Mengyun; ZHANG Sheng; ZHENG Yang; GU Kai; YANG Qundi; RUAN Ye; WANG Yuheng; YAN Qinghua; YANG Qinping; FU Chen; YU Rong; et al. (Guangxi Yike Daxue xuebao)
The aggravation of population aging has made the pressure of chronic disease prevention and treatment increasingly prominent and faced unprecedented challenges. The Shanghai Municipal Government has always attached great importance to the prevention and treatment of chronic diseases and has achieved good results, establishing a government-led, multi-sectoral and community-wide mechanism for the prevention and treatment of chronic diseases, a"four-in-one"model for the comprehensive prevention and treatment of chronic diseases, and an urban and municipal-level chronic disease health management information system. In recent years, Shanghai has built an integrated community health management model based on the"health-center"service strategy, continuously improving and optimising the connotation of the model through the introduction of specifications for the comprehensive prevention and treatment of chronic diseases, the improvement of the chronic disease health management information system and the promotion of the construction of chronic disease management center, as well as the exploration of integration at the three levels of technology, data and services. The model has been implemented with remarkable results, and the integrated community health management model has been implemented and deeply promoted throughout the city, completing the health risk assessment of 2, 176, 100 people (including 619, 900 people with co-morbidities follow-up services), carrying out the discovery and management of high-risk population, and increasing the number of people served by a factor of 9 times. At the same time, 72 community chronic disease management centers have been built, and standardized services have been provided for 3.9 million times, covering 810, 000 individuals. The detection rate of abnormalities in blood pressure, blood glucose and other indicators has increased by 10% to 20% compared with the norm, with better health economics benefits. These centers have been incorporated into many policies such as the Healthy Shanghai Initiative and Community Health Service Capacity Enhancement, and are gradually promoted to the Yangtze River Delta region. In the future, efforts will focus on optimizing the integrated community chronic disease health management model. Online and offline synergistic intervention services will be built based on big data applications. Additionally, an evaluation index system will be established to improve the assessment of comprehensive prevention and treatment services for chronic diseases.